Multidimensional Poverty in Indonesia: The Role of Economic, Social, Educational, and Political Factors - Rama, Ali; Putri, Poppy Secilia; Mynbayeva, Elmira (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Research Originality: This study advances the field by employing a comprehensive, multidimensional framework that examines the synergistic interactions between economic, social, educational, and political factors. This study also provides a more nuanced and evidence-based perspective on poverty dynamics, moving beyond the oversimplified, single-dimensional analyses that have dominated prior scholarship. Research Objectives: This study aims to examine the impact of educational participation, crime rates, unemployment, access to Islamic financing, and the democracy index on poverty levels in Indonesia. Research Methods: Panel data from 2015 to 2022 is examined using a fixed effects model to identify the key determinants of poverty. Empirical Results: The findings indicate that higher net enrolment rates and increased access to Islamic financing significantly contribute to poverty reduction y, while rising crime rates and unemployment are associated with increased poverty levels. Interestingly, the democracy index shows no statistically significant effect on poverty during the examined period. Implications: The findings have significant policy relevance, emphasizing the need to enhance access to quality education, promote job creation, and expand Islamic financing as an inclusive economic tool. JEL Classification: I32, E24, G21